Pengembangan Pendidikan Anak Usia Dini (PAUD) dan Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) pada Masyarakat di Lingkungan Ra-Al Kautsar, Tangerang Selatan: Pengabdian - Sandri, Muhamad; Hija Sabila, Ila; Azzahra Qotrunnada, Fildra; Nur Septianawati, Luluk; Suryo Aditiya, Dimas; Andrian, Aries; Hendrico Abadi, Muhammad; Fahri, Wiliam; Cahya Mardani, Heri; Hakiki, M.Rifki; Seti Utami, Sulistyo (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Implementation of the Clean and Healthy Living Behavior (PHBS) program at RA Al - Kautsar, South Tangerang, which was carried out by students of the Real Work Lecture (KKN) Synergi 29 Group. The main objective of this program is to increase the awareness and understanding of students and the community regarding the importance of maintaining a healthy and clean environment. Through various activities, including the provision of supporting facilities such as portable sinks and trash bins, as well as conducting seminars for parents and teachers, this program aims to create an environment that supports healthy living behavior. The results of these activities show that the active involvement of students, parents, and the community is crucial in supporting the success of the PHBS program. In addition, the greening program implemented also contributes to fostering a sense of responsibility for the environment. The dedication is expected to make a positive contribution to the development of health education at the PAUD level and become a reference for similar programs in the future.